Biosortion of Cr(VI) from Aqueous Solutions Using Chemically Modified Okra Powder - Joelington do C. Conceição; Antônio Santos Silva; Antônio Wilson M. de C. Costa; Antônio Wilson M. de C. Costa; Edilson de Jesus; Victor Hugo S. Ramos (Journal of Basic & Applied Sciences, 2021)
The main objective of this work was to use the okra powder modified with citric acid as biosorbent for the removal of Cr(VI) from aqueous solutions. Samples of Cr(VI) solution were prepared by diluting the 100 ppm solution diluted from the 1000 ppm stock solution prepared with K2Cr2O7. The determination of Cr(VI) was performed spectrophotometrically by the method of complexation with 1,5-diphenylcarbazide, measuring the absorbance at a 540 nm wavelength. The experiments were conducted at 25 ± 1 °C; 2, 5, 7 and 8 initial pH; 10-240 minutes contact time and 0.05 g of adsorbent. The Freundlich and Langmuir models were used to fit the experimental data. The Freundlich model provided R2=0.9599, indicating adsorption on heterogeneous conditions. Analysis of fluorescence of X-rays, SEM and FTIR were used to prove the okra powder efficiency in the removal of Cr(VI) from aqueous solutions.